Spectral analysis of the chemical composition of the incident meteor on 02/01/2023 - Agenor, Matheus; Langhi, Rodolfo (Cadernos de Astronomia, 2023)
In Brazil, we do not have many researchers working in meteor spectroscopy, which is why the work developed can be considered pioneering. For this research, a video meteor monitoring station was installed, similar to those used by the BRAMON within the PATRICIA project, with a diffraction grating attached to the camera, allowing the capture of a meteor to reveal its spectrum. A Samsung surveillance camera model SCB 2000 and a 500 lines/mm diffraction grating were used for the capture. On January 2, 2023, at 6:53 (UTC), the camera linked to the present project captured a relatively bright meteor. Through this capture, and with the aid of the Rspec software, it was possible to analyze the spectrum emitted by the meteor's ablation, and by studying the intensity peaks, it was possible to determine the chemical composition of the meteor. We observed the presence of Iron, Chromium, Calcium, Nickel, Magnesium, Nitrogen, and Oxygen, all in their neutral forms, except for Nitrogen, which was found in its ionized form.
Keywords: meteor spectroscopy; spectrum; chemical composition